Multiple forms of maturation-promoting factor in unfertilized Xenopus eggs. - Kuang, J (1991)
Maturation-promoting factor (MPF), which is functionally defined by its ability to induce frog oocyte maturation independent of protein synthesis, is hypothesized to be the mitotic inducer in eukaryotic cells. Previous studies have demonstrated that the cdc2 protein kinase complex (p34cdc2-cyclin) meets the criteria for MPF. In the present study, we show that MPF activity in extracts of unfertilized Xenopus eggs can be resolved into three fractions by Q-Sepharose chromatography. Of the total MPF activity recovered, approximately 20% was in the flow-through fraction that was accounted for by the cdc2 kinase complex, approximately 40% was in the 0.2 M NaCl eluate, and the remaining approximately 40% was in the 0.5 M NaCl eluate. Neither eluate contained cdc2 kinase, but each could activate cdc2 kinase upon microinjection into Xenopus oocytes. The MPF activity in the two eluates, but not in the flow-through fraction, could be depleted by the mitosis-specific monoclonal antibody MPM-2. This antibody has been shown to inhibit Xenopus oocyte maturation and deplete MPF activity from mature oocyte extract but does not recognize the cdc2 kinase complex. The three MPFs differed in apparent molecular size, H1 kinase activity, and stability at 4 degrees C. We propose that MPF activity in unfertilized Xenopus eggs resides in at least three different molecular species, the combined activities of which may be required for autoamplification of MPF.